GROWTH AND MORPHOLOGICAL DIVERSITY OF 16 SINENSIS TEA CLONES (Camellia sinensis (L.) Kuntze var. sinensis) DURING SEEDLING PHASE - Syahrul Firdaus A. L; Ida Adviany; Heri Syahrian; Vitria P. Rahadi; M. Khais Prayoga (UIN Sunan Gunung Djati Bandung, 2026)
This study investigated the morphological diversity and population structure of 16 Sinensis tea clones (Camellia sinensis (L.) Kuntze var. sinensis) during the nursery phase to support superior variety development. The research was conducted at the Gambung Tea and Kina Research Center, West Java, using morphological and growth trait analysis. Data were analyzed using Principal Component Analysis (PCA) and Cluster Analysis. The results revealed significant morphological variation among the clones, particularly in leaf number, shoot color, and leaf blade morphology. PCA indicated that 88% of the phenotypic variation was explained by five principal components, with the number of leaves and second leaf color at the p+2 position identified as the most influential traits for clonal differentiation. Cluster analysis classified the 16 clones into two distinct kinship groups, with the second group comprising 81.25% of the tested population. These findings provide essential insights into the genetic and morphological landscape of Sinensis tea clones, establishing a robust framework for parent selection and future breeding programs aimed at producing high-quality varieties for the international green tea market.